A Novel Dual-cre Motif Enables Two-Way Autoregulation of CcpA in Clostridium acetobutylicum - Zhang, Lu (Appl Environ Microbiol, 2018)
The master regulator CcpA (catabolite control protein A) manages a large and complex regulatory network that is essential for cellular physiology and metabolism in Gram-positive bacteria. Although CcpA can affect the expression of target genes by binding to a cis-acting catabolite-responsive element (cre), whether and how the expression of CcpA is regulated remain poorly explored. Here, we report a novel dual-cre motif that is employed by the CcpA in Clostridium acetobutylicum, a typical solventogenic Clostridium species, for autoregulation. Two cre sites are involved in CcpA autoregulation, and they reside in the promoter and coding regions of CcpA. In this dual-cre motif, cre(P), in the promoter region, positively regulates ccpA transcription, whereas cre(ORF), in the coding region, negatively regulates this transcription, thus enabling two-way autoregulation of CcpA. Although CcpA bound cre(P) more strongly than cre(ORF) in vitro, the in vivo assay showed that cre(ORF)-based repression dominates CcpA autoregulation during the entire fermentation. Finally, a synonymous mutation of cre(ORF) was made within the coding region, achieving an increased intracellular CcpA expression and improved cellular performance. This study provides new insights into the regulatory role of CcpA in C. acetobutylicum and, moreover, contributes a new engineering strategy for this industrial strain. IMPORTANCE CcpA is known to be a key transcription factor in Gram-positive bacteria. However, it is still unclear whether and how the intracellular CcpA level is regulated, which may be essential for maintaining normal cell physiology and metabolism. We discovered here that CcpA employs a dual-cre motif to autoregulate, enabling dynamic control of its own expression level during the entire fermentation process. This finding answers the questions above and fills a void in our understanding of the regulatory network of CcpA. Interference in CcpA autoregulation leads to improved cellular performance, providing a new useful strategy in genetic engineering of C. acetobutylicum. Since CcpA is widespread in Gram-positive bacteria, including pathogens, this dual-cre-based CcpA autoregulation would be valuable for increasing our understanding of CcpA-based global regulation in bacteria.